The Political and Moral Imperatives of the Bandung Conference of 1955 : the Reactions of the US, UK and Japan. - Ampiah, Kweku (BRILL, 2007)
Now fifty years on, with significantly more primary references available, Kweku Ampiah's study provides a much-needed in-depth re-evaluation of the conference as a whole, focusing in particular on the external influences and preoccupations impacting on the participants seen through three case studies involving the US, UK and Japan.